2010
DOI: 10.1111/j.1364-3703.2010.00643.x
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry‐based metabolomics application to identify quantitative resistance‐related metabolites in barley against Fusarium head blight

Abstract: Quantitative resistance is generally controlled by several genes. More than 100 resistance quantitative trait loci (QTLs) have been identified in wheat and barley against Fusarium head blight (FHB), caused by Gibberella zeae (anamorph: Fusarium graminearum), implying the possible occurrence of several resistance mechanisms. The objective of this study was to apply metabolomics to identify the metabolites in barley that are related to resistance against FHB. Barley genotypes, Chevron and Stander, were inoculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
174
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(192 citation statements)
references
References 57 publications
15
174
3
Order By: Relevance
“…Metabolic profiles were developed using a LC hybrid MS system, described in a recently published study by Bollina et al (2010), with a few modifications. The samples were loaded into a 96 well plate and analyzed using an LC-ESI-LTQ Orbitrap (Thermo Fisher, Waltham, MA).…”
Section: Metabolite Analysis Using Lc-esi-ltq-orbitrapmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic profiles were developed using a LC hybrid MS system, described in a recently published study by Bollina et al (2010), with a few modifications. The samples were loaded into a 96 well plate and analyzed using an LC-ESI-LTQ Orbitrap (Thermo Fisher, Waltham, MA).…”
Section: Metabolite Analysis Using Lc-esi-ltq-orbitrapmentioning
confidence: 99%
“…In the study presented here, metabolomics technology based on LC coupled to a hybrid mass spectrometer (LC-ESI-LTQ-Orbitrap) was employed to phenotype resistance in two-row barley with cleistogamous florets, against G. zeae. Our earlier paper addressed resistance in six-row barley genotypes with chasmogamous florets (Bollina et al 2010). Under field conditions, the former is more resistant than the latter.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has been applying this technology to the detection and structure elucidation of metabolites in plants upon 105 treatment with a wide range of biotic and abiotic stress agents (Choi et al, 2004;Simoh et al, 2009;Jahangir et al, 2009;Mirnezhad et al, 2010;Simoh et al, 2010). In recent years, very detailed NMR metabolomic studies on both compatible and incompatible plant-pathogen interactions have been reported (Lima et al, 2010;Bollina et al, 2010;Ward et al, 2010;Jones et al, 2011). 110…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies already indicate that a complex network of secondary metabolites is influenced by biotic stress challenges. Next to phenylpropanoids, including flavonoids [51][52][53], alkaloids [54,55], terpenoids [52], and fatty acids [56] are known to be up-regulated [10]. In addition, activities [35].…”
Section: From Biotic Stress Metabolomics To Metabolic Responsementioning
confidence: 99%